Prevalence and risk estimates of Cryptosporidium oocysts infection associated with consumption of raw-eaten vegetables in Maiduguri metropolis LGAs, Northeast Nigeria - Saidu, A. S.; Mohammed, S.; Adamu, S. G.; Sadiq, M. A.; Tijjani, A. O.; Musa, H. I.; Jajere, S. M.; Goni, M. D.; Muhammed, A.; Idriss, M. D. (Nature Research, 2023)
Cryptosporidium is one of the most important protozoan parasitic pathogens, and it is a common cause of diarrhoea in humans, domestic animals, and wild vertebrates and has serious public health threats. A cross-sectional study was designed to determine the prevalence of Cryptosporidium oocysts in raw-eaten vegetables in Maiduguri Metropolitan Council (MMC) and Jere Local Government Areas (LGAs). A total of 400 samples were collected from four (4) different locations, namely Tashan Bama, Gomboru, and Monday Markets (n = 100), while fifty (n = 50) each from 202-Vegetable-Vendors and Unimaid Commercials. A total of 16 visits were conducted in all the sampling areas (twenty-five samples per visit). The Cryptosporidium oocysts were detected using the Modified Ziehl–Neelsen Staining Technique. The locations, sources, and types of raw-eaten vegetables were also assessed. The oocysts were confirmed (100×) as bright pink spherules. Data generated were analyzed using IBM-SPSS V23.0, and p ≤ 0.05 was considered significant. Out of the total samples (n = 400) analyzed, cabbage appeared to have the highest number of 10 (12.5%) of Cryptosporidium oocysts detected, while Tomato and garden egg had 9 (11.3%) and 1 (1.2%), respectively. There was a statistically significant association (χ2 = 12.5, P = 0.014) between the presence of Cryptosporidium oocysts in raw-eaten vegetables and vegetable types. Among the sources of the vegetables sampled, Alau had the highest number of Cryptosporidium oocysts, 15 (12.5%), followed by Kilari-Abdullahi and Zabarmari sources with 4 (10.0%) and 4 (5.0%), respectively. However, Jetete appeared to have the least number 2 (2.5%) of oocysts, and there was a statistically significant association (χ2= 10.4, P = 0.034) between the presence of Cryptosporidium oocysts and the sources of vegetables and fruits. The study concludes that the raw-eaten vegetables sampled from Maiduguri Metropolis were contaminated with Cryptosporidium oocysts. The study recommends that all raw-eaten vegetables should be from cleaned sources and washed before consumption. Consumers should be enlightened on the hygienic measures in the food chain in line with the Hazard Analysis and Critical Control Points (HACCP) principles.